Debates sobre bicameralidad: perspectivas y retos - Rubio Correa, Marcial; Pomareda Muñoz, Diego; Lovatón Palacios, David (Pontificia Universidad Católica del Perú, 2025)
This round table discussion examines the return to bicameralism, a reform that has raised new doubts regarding its viability. Although Peru was governed under this system in the past, the main current criticism lies in the fact that this measure was approved despite its rejection by the population in a referendum, which seriously compromises its legitimacy. The authors agree that this change is risky: it alters the balance of powers in favor of the Parliament, increases public spending, and does not ensure faster processes. Ultimately, this reform does not resolve the main problem: Parliament’s lack of representation, a debate from which the reader may draw their own conclusions.

En esta mesa redonda se examina el regreso de la bicameralidad, una reforma que ha generado nuevas dudas sobre su viabilidad. Aunque, en el pasado, el Perú estuvo regido por este sistema, el mayor cuestionamiento actual reside en que esta medida se aprobó pese a su rechazo por la población en referéndum, lo que afecta seriamente su legitimidad. Los autores coinciden en que el cambio es riesgoso: altera el equilibrio de poderes a favor del Congreso, aumenta el gasto público y no asegura procesos más rápidos. En el fondo, esta reforma no resuelve el problema principal, que es la falta de representatividad del Parlamento, un debate sobre el cual el lector podrá sacar sus propias conclusiones.
Debates on bicameralism: perspectives and challenges
Keywords: Bicameralism; Constitutional reform; Senate; Deputies; Balance of Powers; Constitutional law; Legitimacy; Bicameralidad; Reforma constitucional; Senado; Diputados; Equilibrio de poderes; Derecho Constitucional; Legitimidad; https://purl.org/pe-repo/ocde/ford#5.05.01